(untitled) (International Journal of Engineering and Computer Science, 2017)
This abstract tells about a Wireless Technological Device which is popular for extremely Low Power, and Low Bit Rate Wireless PAN Technology called ZigBee. ZigBee is designed for wireless Automation and other lower data tasks, such as smart home automation and remote monitoring. ZigBee is a low-cost, low-power, wireless mesh networking standard. The low cost allows the technology to be widely deployed in wireless control and monitoring applications, the low power usage allows longer life with smaller batteries, and the mesh networking provides high reliability and larger range. Due to the low-cost and low-power usage this wireless technology is widely used in Home Automation, Smart Energy, Telecommunication Applications, Personal Home, Hospital Care. ZigBee enables new opportunities for wireless sensors and control networks. ZigBee is standard based, low cost, can be used globally, reliable and self healing, supports large number of nodes, easy to deploy, very long battery life and secure. 1. [1]